ISupport-Brasil: Cross-cultural adaptation of the content included in the iSupport program for caregivers of people who have dementia. (April 2023) - Monteiro, Diana Q.; Ottaviani, Ana C.; Campos, Camila R. F.; Barham, Elizabeth J.; Oliveira, Déborah; da Cruz, Keila C. T.; Pavarini, Sofia C. I.; de Souza Orlandi, Fabiana; Zazzetta, Marisa S.; Jacinto, Alessandro F.; Corrêa, Larissa; Gratão, Aline C. M.
Objective: Examine the process of culturally adapting the content of the World Health Organization iSupport program for family caregivers of people living with dementia in Brazil. Method: This is a multicenter and methodological study to cross-culturally adapt the iSupport program. Initially, the content of the iSupport program was translated into Brazilian Portuguese by professional translator trained in Psychology, with mastery of the original language of the content (English). Focus groups were then held with caregivers/former caregivers of people who have dementia ( n = 24) and health professionals specialized in aging ( n = 24). The participants had access to part of the iSupport material for analysis purposes. Semi-structured interviews were conducted between June and September 2019. All the interviews were recorded and transcribed in full for subsequent analysis. All the ethical aspects were respected. Results: The translator implemented some cross-cultural adaptations, such as substituting 69 proper names used in the original version by names of different Brazilian regions. In relation to the analysis of the material and comments from the focus groups, in general, all the participants had positive opinions about the material included in iSupport. Some changes were suggested in relation to the terminology and examples given in the modules to better fit the Brazilian culture and health systems, and links to relevant pages of the local Alzheimer's association were included. All the linguistic and cultural adaptations proposed were systematically documented and duly justified in structured forms provided by the World Health Organization, which approved all of them after verification of fidelity. Conclusion: The product of this research is the first version of the iSupport-Brasil program and the inclusion of its content in a digital platform. For the most part, the content offered in iSupport proved to be an important online tool to provide support and diverse information to the caregivers of people who have dementia.